Increase of Smoked-Fish plant income in Sumurgung, Tuban Regency Through the Introduction of equipment Production, Smoked-Fish with closed system. - Asep Awaludin Prihanto, S.Pi., MP. (Journal of Innovation and Applied Technology, 2019)
Tuban Regency is one of the regencies in East Java that has abundant natural resources, especially in the field of fisheries. Catfish are quite popular among the people in Tuban Regency, but when the stock surplus or harvest is high, the selling price of catfish at the level of the community of farmers has decreased and resulted in decreased profits. Based on these conditions, we are optimizing the processing of catfish in order to increase the value of the benefits obtained by diversifying processed catfish products in the form of smoked catfish. Smoked fish has higher value because it can preserve fish and give a distinctive taste to the product. The purpose of this empowerment study is to compare income between diversifying and selling in fresh form.